A comprehensive review of probiotics and human health-current prospective and applications - Sarita, Bhutada; Samadhan, Dahikar; Hassan, Md Zakir; Kovaleva, Elena G. (Frontiers in Microbiology, 2025)
The beneficial properties of probiotics have always been a point of interest. Probiotics play a major role in maintaining the health of Gastrointestinal Tract (GIT), a healthy digestive system is responsible for modulating all other functions of the body. The effectiveness of probiotics can be enhanced by formulating them with prebiotics the formulation thus formed is referred to as synbiotics. It not only improves the viability and stability of probiotic cells, but also inhibits the growth of pathogenic strains. Lactobacillus and Bifidobacterium spp. are most commonly used as probiotics. The other microbial spp. that can be used as probiotics are Bacillus, Streptococcus, Enterococcus, and Saccharomyces. Probiotics can be used for the treatment of diabetes, obesity, inflammatory, cardiovascular, respiratory, Central nervous system disease (CNS) and digestive disorders. It is also essential to encapsulate live microorganisms that promote intestinal health. Encapsulation of probiotics safeguards them against risks during production, storage, and gastrointestinal transit. Heat, pressure, and oxidation eradicate probiotics and their protective qualities. Encapsulation of probiotics prolongs their viability, facilitates regulated release, reduces processing losses, and enables application in functional food products. Probiotics as microspheres produced through spray drying or coacervation. This technique regulates the release of gut probiotics and provides stress resistance. Natural encapsulating materials including sodium alginate, calcium chloride, gel beads and polysaccharide promoting safeguards in probiotics during the digestive process. However, several methods including, spray drying where liquid is atomized within a heated air chamber to evaporate moisture and produce dry particles that improves the efficacy and stability of probiotics. Additionally, encapsulating probiotics with prebiotics or vitamins enhance their efficacy. Probiotics enhance immune system efficacy by augmenting the generation of antibodies and immunological cells. It combats illnesses and enhances immunity. Recent studies indicate that probiotics may assist in the regulation of weight and blood glucose levels and influence metabolism and insulin sensitivity. Emerging research indicates that the “gut-brain axis” connects mental and gastrointestinal health. Probiotics may alleviate anxiety and depression via influencing neurotransmitter synthesis and inflammation. Investigations are underway about the dermatological advantages of probiotics that forecasting the onsite delivery of probiotics, encapsulation is an effective technique and requires more consideration from researchers. This review focuses on the applications of probiotics, prebiotics and synbiotics in the prevention and treatment of human health.